CONSISTENCY OF ENDOMETRIAL SAMPLING WITH SUBSEQUENT HYSTERECTOMY FINDINGS IN DUHOK- IRAQ - Abdulkareem, Kawar Sardar; Raziq, Alaa Hani (International Journal of Psychosocial Rehabilitation, 2020)
Endometrial sampling is one of the commonest diagnostic procedures and upon its results various actions will be set. This study aimed to compare the results of endometrial biopsy and proceeding hysterectomy and to determine the value of endometrial biopsy in the diagnosis of various pathologies. This study is a comparative one between the results of endometrial sampling and hysterectomy and included 200 patients from 1-1-2012 until 1-1-2018 in Duhok City-Iraq. Pregnancy related disorders were excluded. Histological reports and slides were retrieved from the bank of data in the central laboratory of Duhok City. Results of both procedures were put in three categories; the non-significant differences, the significant and consistent findings and the significant and inconsistent results. The reliability of endometrial biopsy was determined for carcinoma and hyperplasia. In addition, upgrading and downgrading of certain disorders was calculated. For the significant and inconsistent category, intra and inter-observer variability were estimated. The age of the included patients ranged from 27-80 years with a mean of 53.5 years ± (26.5). There were non-significant differences in (53%) of cases, significant and consistent results in 9% of cases and significant but inconsistent results in 38% of cases. In the latter group the intra-observer and inter-observer variabilities were (22.4%) and (77.6%) respectively. For carcinoma cases, endometrial sampling was reliable in (100%) of cases but for hyperplasia, correct diagnosis was given in only 30.8% of cases. Significant and inconsistent results of endometrial biopsy when compared to hysterectomy were found in (38%) cases a finding should make the gynecologists deal with awareness when making a proceeding decision to utilize other investigations modalities in conjunction. Regarding endometrial carcinoma, endometrial sampling is a reliable diagnostic procedure but this reliability is diminished for other pathologies.